KARAKTERISTIK PASIEN SKABIES DI SMF ILMU KESEHATAN KULIT DAN KELAMIN RSUD MANDAU KABUPATEN BENGKALIS PERIODE JANUARI 2021-JANUARI 2022 - Almamira Oktamara; Lenisha Tantia; Santry Indriani Lestari; Viola Anggraini Asrizal; Tri Harianti; Prayoga Eko Nuryadi (Collaborative Medical Journal, 2023)
Scabies is a contagious skin disease caused by sarcoptes scabiei hominis varieties (mites or small lice). Scabies cause itching due to female mites living in the epidermis for 30 days of cycles. The typical symptoms arising from this mite infestation are shallow burrows such as tunnels due to sarcoptes scabiei hominist varieties that penetrate the skin, severe itching in the day, general rashes can occur in most body or limited to certain parts. This study has the aim of knowing the prevalence of scabies patients in Mandau Regional Hospital in Bengkalis Regency as well as a picture of scabies patients based on age, gender, occupation and residence. This type of research is descriptive retrospective, researchers use secondary data originating from the record of the medical record of scabies patients at SMF Skin and Gender Health Sciences Hospital Mandau Bengkalis Regency for January 2021 to January 2022 and uses Purposive Sampling techniques in sampling. The results of this study found that men suffer more scabies as many as 318 patients (50.88%) out of 625 patients, patients aged 6-11 years suffered the most scabies, namely 148 patients (23.68%), based on the highest job It happened in students, as many as 273 (43.68%) as well as the most common place to live in the house, namely 537 patients (85,92%).